A review on various temperature-indication methods for Li-ion batteries. (15th April 2019) - Raijmakers, L.H.J.; Danilov, D.L.; Eichel, R.-A.; Notten, P.H.L.
Highlights: The working principle of Li-ion batteries is explained. An overview is given on heat generation principles in Li-ion batteries. All traditional and new battery temperature measurement methods are reviewed. The challenges in battery temperature measurements are highlighted. A comparative analysis is made for Li-ion battery temperature measurements. Abstract: Temperature measurements of Li-ion batteries are important for assisting Battery Management Systems in controlling highly relevant states, such as State-of-Charge and State-of-Health. In addition, temperature measurements are essential to prevent dangerous situations and to maximize the performance and cycle life of batteries. However, due to thermal gradients, which might quickly develop during operation, fast and accurate temperature measurements can be rather challenging. For a proper selection of the temperature measurement method, aspects such as measurement range, accuracy, resolution, and costs of the method are important. After providing a brief overview of the working principle of Li-ion batteries, including the heat generation principles and possible consequences, this review gives a comprehensive overview of various temperature measurement methods that can be used for temperature indication of Li-ion batteries. At present, traditional temperature measurement methods, such as thermistors and thermocouples, are extensively used. Several recently introduced methods, such as impedance-based temperature indication and fiber Bragg-grating techniques, are under investigation in order to determine if those are suitable for large-scale introduction in sophisticated battery-powered applications.